Comparative Analysis of the Effectiveness of the Faculty Library with the Diponegoro University Library - Rahma, Tika Nadia (Universitas Pendidikan Indonesia, 2023)
Documentation is one word that has been mentioned so far. But actually this word The university library is a supporting institution established to support the activities of the university's academic community where it is located. The university library policy states that the Higher Education library is part of higher education support activities. With the existence of a library, universities can fulfill their obligations to their citizens. The purpose of this study is to find out how enthusiastic the Diponegoro University community is towards the faculty and university libraries. Descriptive qualitative methods were used for this study which passed a questionnaire approach. The results of this study, First, there is a low frequency of visits by users to college libraries, both Diponegoro University libraries and faculty libraries. Second, many respondents stated that faculty libraries do not yet have adequate library service quality, so that users find it difficult to find the information they need. Third, many respondents prefer to visit Diponegoro University libraries to find information.. This research is not perfect but it is hoped that it will be useful for faculty and university librarians to evaluate and develop their respective libraries.